Prevalence and Spectrum of Predisposition Genes With Germline Mutations Among Chinese Patients With Bowel Cancer - Xie, Zhengyong; Ke, Yongli; Chen, Junyong; Li, Zehang; Wang, Changzheng; Chen, Yuhong; Ding, Hongliang; Cheng, Liyang (Frontiers in Genetics, 2022)
Background: Bowel cancer is the third-most common cancer and the second leading cause of cancer-related death worldwide. Bowel cancer has a substantial hereditary component; however, additional hereditary risk factors involved in bowel cancer pathogenesis have not been systematically defined. Materials and Methods: A total of 573 patients with bowel cancer were enrolled in the present study, of whom 93.72% had colorectal cancer (CRC). Germline mutations were integrated with somatic mutation information via utilizing target next-generation sequencing. Results: Pathogenic/Likely Pathogenic (P/LP) germline alterations were identified in 47 (8.2%) patients with bowel cancer and the ratio of the number of these patients with family history was significantly higher in the P/LP group than that noted in the non-pathogenic (Non-P) group. Certain rare germline alterations were noted, such as those noted in the following genes: FANCD2, CDH1, and FLCN. A total of 32 patients (68.1%) had germline alterations in the DNA-damage repair (DDR) genes and homologous recombination (HR) accounted for the highest proportion of this subgroup. By comparing 573 patients with bowel cancer with reference controls (China_MAPs database), significant associations (p < 0.01) were observed between the incidence of bowel cancer and the presence of mutations in APC, ATM, MLH1, FANCD2, MSH3, MSH6, PMS1, and RAD51D. Somatic gene differential analysis revealed a marked difference in 18 genes and a significant difference was also noted in tumor mutation burden (TMB) between germline mutation carriers and non-germline mutation subjects (p < 0.001). In addition, TMB in DDR mutation groups indicated a dramatic difference compared with the non-DDR mutation group (p < 0.01). However, no statistically significant differences in TMB were noted among detailed DDR pathways for patients with bowel cancer, irrespective of the presence of germline mutations. Moreover, a significantly higher level (p < 0.0001) of mutation count was observed in the DDR group from The Cancer Genome Atlas (TCGA) database and the DDR and non-DDR alteration groups displayed various immune profiles. Conclusion: Chinese patients with bowel cancer exhibited a distinct spectrum of germline variants, with distinct molecular characteristics such as TMB and DDR. Furthermore, the information on somatic mutations obtained from TCGA database indicated that a deeper understanding of the interactions among DDR and immune cells would be useful to further investigate the role of DDR in bowel cancer.